(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this article it’s interestingly mentioned that designed as well as created activity of library software programs started during the mid-1980s in India, with the promotion of UNESCO’s CDS/ISIS by the National Information System on Technology and Science (NISSAT). This study examined the usage of integrated library system in academic libraries. The main challenges confronting the libraries include: inadequate funding, inadequate managerial assistance, poor energy supply, etc. The goal of this particular chapter is actually introducing the idea of library automation, integrated associated areas as well as library software. The library automation software is described in detail; extra emphasis has been given just to describe the software features.